Method for preparing battery negative electrode material based on waste scr catalyst and negative electrode material

CN122853443APending Publication Date: 2026-10-02SHANGHAI SHIDONGKOU NO 2 POWER PLANT HUANENG INTERNATIONAL POWER CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610951470.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

这种“先拆解、再分别纯化”的思路由于流程长,在商业上常常亏损

Benefits of technology

1、本发明相比现有技术在回收废SCR催化剂的方法步骤,无需进行复杂的酸碱浸出与重金属分离,流程得到了有效缩短,且全流程无废水产生,实现了工业危废的“全量零排高值化利用”。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122853443A_ABST
    Figure CN122853443A_ABST
Patent Text Reader

Abstract

This invention provides a method for preparing battery anode materials based on spent SCR catalysts, and the anode materials themselves. Belonging to the technical fields of new materials for energy storage batteries and high-value utilization of solid waste, this invention can at least partially solve the problems of cumbersome recycling processes, high purification costs, and heavy secondary pollution associated with existing spent SCR catalysts. This invention sequentially prepares spent SCR micropowder, precursor mixed slurry, and precursor microspheres. By performing a one-step high-temperature solid-phase pyrolysis of the precursor microspheres, the active components such as vanadium, tungsten, and titanium in the spent SCR catalyst are directly converted into a composite anode material applicable to energy storage batteries. This eliminates the need for stepwise purification and separation of each metal component, simplifying the recycling process of spent SCR catalysts, significantly reducing recycling costs, and avoiding secondary pollution caused by large amounts of acidic and alkaline wastewater generated during multi-step purification processes. The anode material prepared by this invention achieves low-cost, high-value utilization of spent SCR catalysts, combining environmental and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of new materials for energy storage batteries and high-value utilization of solid waste, specifically involving a method for preparing battery anode materials based on waste SCR catalysts and the anode materials themselves. Background Technology

[0002] With the explosive growth of the new energy industry, the demand for low cost and high safety in energy storage batteries is becoming increasingly urgent. Sodium-ion batteries, due to the abundant and widely distributed sodium resources, are considered one of the most promising next-generation large-scale energy storage technologies. Among various anode materials for sodium-ion batteries, titanium dioxide (TiO2) has attracted widespread attention due to its non-toxicity, small volume expansion (only about 4%), and safe operating potential (about 0.7V vs. Na / Na+). However, pure TiO2 has extremely low intrinsic electronic conductivity and ion diffusion rate, resulting in poor rate performance and actual discharge capacity. Modification is usually required through transition metal doping (such as V and W doping) and carbon coating.

[0003] On the other hand, industrially generated spent SCR catalysts (mainly composed of TiO2, naturally containing V and W components) typically face problems such as cumbersome recycling processes and high purification costs. Current technologies for recycling spent catalysts mostly involve painstakingly extracting and separating the V and W components, then repurifying the TiO2. This "disassemble first, then purify separately" approach is commercially unprofitable due to its lengthy process. If we could break with convention and treat the V and W active components in spent SCR catalysts not as "impurities" but directly as "modifying dopants," transforming the entire catalyst into a high-performance sodium-ion battery anode material in a one-step process, we could achieve a transformation from solid waste to high-value energy storage materials.

[0004] Therefore, a method for preparing battery anode materials based on waste SCR catalysts and the anode materials are proposed. Summary of the Invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art, and provides a method for preparing battery anode materials based on waste SCR catalysts and the anode materials themselves.

[0006] This invention provides a method for preparing battery anode materials based on spent SCR catalysts, the method comprising the following steps: S1. Pre-treat the waste titanium-based SCR catalyst containing vanadium and tungsten components to obtain waste SCR micro powder; S2. A precursor mixture slurry is prepared by using the waste SCR micro powder, soluble carbon source and sodium source; S3. Spray dry the precursor mixture slurry to obtain precursor microspheres; S4. The precursor microspheres are placed in an inert atmosphere furnace and subjected to one-step high-temperature solid-phase pyrolysis to obtain the anode material.

[0007] Furthermore, in step S1, the particle size of the waste SCR powder is ≤45μm.

[0008] Further, in step S2, the soluble carbon source is any one or more of glucose, sucrose, citric acid, or polyethylene glycol; the sodium source is any one of sodium carbonate, sodium acetate, or sodium hydroxide.

[0009] Further, in step S2, the mass ratio of the waste SCR micro powder, soluble carbon source and sodium source is 10:(2-5):(0.5-1.5).

[0010] Further, in step S2, the preparation method of the precursor mixed slurry includes the following steps: dissolving or dispersing the waste SCR derivative, soluble carbon source and sodium source together in deionized water, and obtaining the precursor mixed slurry by ultrasonic dispersion.

[0011] Furthermore, the ultrasonic dispersion power is 300W to 600W, and the ultrasonic time is 40min to 80min; the solid content of the precursor mixture slurry is 13% to 25%.

[0012] Furthermore, in step S3, the inlet air temperature of the spray dryer is 180℃~220℃, and the outlet air temperature is 90℃~110℃.

[0013] Further, in step S4, the one-step high-temperature pyrolysis step includes: heating the inert atmosphere furnace to 650℃~800℃ at a heating rate of 5℃ / min to pyrolyze the precursor microspheres, and holding the temperature for 4h~8h.

[0014] Another aspect of the present invention provides a battery anode material prepared based on waste SCR catalyst, comprising vanadium and tungsten co-doped titanium dioxide grains, wherein the titanium dioxide grains are in situ encapsulated by an amorphous carbon layer.

[0015] Furthermore, at a current density of 0.1 A / g, the initial discharge specific capacity of the negative electrode material is ≥260 mAh / g, and the capacity retention rate after 500 cycles is ≥91%.

[0016] The beneficial effects of this invention are as follows: 1. Compared with the prior art, the present invention eliminates the need for complex acid and alkali leaching and heavy metal separation in the method and steps of recycling waste SCR catalysts, effectively shortening the process and generating no wastewater throughout the entire process, thus realizing the "full-volume zero-discharge high-value utilization" of industrial hazardous waste.

[0017] 2. The battery anode material prepared by the present invention exhibits excellent electronic / ionic dual conduction characteristics due to the high molecular-level dispersion of vanadium (V) and tungsten (W) elements in the original SCR catalyst. After in-situ pyrolysis, the vanadium (V) and tungsten (W) co-doped titanium dioxide anode formed exhibits excellent molecular / ionic dual conduction characteristics, overcoming the shortcomings of low capacity and poor conductivity of ordinary titanium-based anodes. Attached Figure Description

[0018] Figure 1 This is a schematic flowchart illustrating the steps of a method for preparing battery anode materials based on waste SCR catalyst according to a specific embodiment of the present invention. Detailed Implementation

[0019] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0020] like Figure 1 As shown in the figure, the method for preparing battery anode materials based on waste SCR catalyst provided by the specific embodiment of the present invention includes the following steps: S1, pretreating waste titanium-based SCR catalyst containing vanadium and tungsten components to obtain waste SCR micro powder; S2, preparing a precursor mixed slurry by means of the waste SCR micro powder, a soluble carbon source and a sodium source; S3, spray drying the precursor mixed slurry to obtain precursor microspheres; S4, placing the precursor microspheres in an inert atmosphere furnace and performing one-step high-temperature solid-phase pyrolysis to obtain the anode material.

[0021] Furthermore, in step S1, the particle size of the waste SCR powder is ≤45μm.

[0022] Based on the above basic implementation method, in step S1, the waste titanium-based SCR catalyst containing vanadium and tungsten active components is mechanically ball-milled to remove the surface dust of the waste titanium-based SCR catalyst and obtain waste SCR micro powder with a particle size of no more than 45 μm.

[0023] Further, in step S2, the soluble carbon source is any one or more of glucose, sucrose, citric acid, or polyethylene glycol; the sodium source is any one of sodium carbonate, sodium acetate, or sodium hydroxide.

[0024] Further, in step S2, the mass ratio of the waste SCR micro powder, soluble carbon source and sodium source is 10:(2-5):(0.5-1.5).

[0025] Further, in step S2, the preparation method of the precursor mixed slurry includes the following steps: dissolving or dispersing the waste SCR derivative, soluble carbon source and sodium source together in deionized water, and obtaining the precursor mixed slurry by ultrasonic dispersion.

[0026] In the above embodiments, the soluble carbon source is glucose, the sodium source is sodium acetate, and the deionized water is distilled water. The waste SCR micro powder prepared in step S1, glucose and sodium acetate are added to a preset volume of distilled water at a mass ratio of 10:(2~5):(0.5~1.5) to maintain the overall solid content at 26.5%~26.7%. Then, ultrasonic dispersion is performed to obtain a precursor mixture slurry that is uniformly suspended and does not separate into layers.

[0027] Furthermore, the ultrasonic dispersion power is 300W to 600W, and the ultrasonic time is 40min to 80min; the solid content of the precursor mixture slurry is 13% to 25%.

[0028] In the above embodiment, in step S3, the precursor mixture slurry obtained in step S2 is fed into a spray dryer for drying. The inlet air temperature, outlet air temperature, and atomizing disc rotation speed of the spray dryer are set. After drying, the precursor microspheres are collected.

[0029] Furthermore, in step S3, the inlet air temperature of the spray dryer is 180℃~220℃, and the outlet air temperature is 90℃~110℃.

[0030] In the above embodiment, in step S4, the inert atmosphere furnace is a tube furnace. The precursor microspheres collected in step S3 are placed in the tube furnace, and high-purity nitrogen or high-purity argon is introduced for protection. The atmosphere in the tube furnace is heated to the preset temperature at a heating rate of 5°C / min, and then pyrolyzed at a constant temperature. After natural cooling to room temperature, the negative electrode material is obtained. The negative electrode material includes vanadium and tungsten co-doped titanium dioxide grains, and the titanium dioxide grains are in situ wrapped by an amorphous carbon layer.

[0031] Further, in step S4, the one-step high-temperature pyrolysis step includes: heating the inert atmosphere furnace to 650℃~800℃ at a heating rate of 5℃ / min to pyrolyze the precursor microspheres, and holding the temperature for 4h~8h.

[0032] In the above embodiments, the uniformly distributed tungsten trioxide (WO3) and vanadium pentoxide (V2O5) components in the spent SCR catalyst undergo in-situ reduction and migration of vanadium (V) and tungsten (W) elements into the titanium dioxide (TiO2) lattice during the one-step high-temperature solid-state pyrolysis process. The doping of the metallic elements vanadium (V) and tungsten (W) significantly reduces the band gap width of TiO2, thereby improving the conductivity of the anode material. Simultaneously, the in-situ pyrolysis of the outer carbon source forms a highly conductive carbon network, which not only further enhances the intrinsic electronic conductivity of the entire electrode but also effectively buffers the volumetric strain generated during the sodium insertion / extraction process of titanium dioxide, preventing electrode structure breakage and pulverization, and ensuring the structural stability of the electrode during long-term cycling. This route, which uses the natively dispersed V / W of spent SCR catalysts as a doping source and transforms them into modified anode materials in one step, breaks away from the traditional approach of "separation, purification, and reuse" in the recycling of spent SCR catalysts. It significantly shortens the preparation process, avoids the generation of large amounts of acid and alkali waste liquids, and realizes the low-cost, full-volume, and high-value utilization of industrial hazardous waste. The resulting anode material has both low cost and excellent electrochemical performance, making it suitable as an anode material for large-scale sodium-ion batteries for energy storage, and has good prospects for industrial application.

[0033] In another embodiment, the present invention also provides a battery anode material prepared based on waste SCR catalyst, comprising vanadium and tungsten co-doped titanium dioxide grains, wherein the titanium dioxide grains are in situ encapsulated by an amorphous carbon layer.

[0034] Specifically, at a current density of 0.1 A / g, the initial discharge specific capacity of the negative electrode material is ≥260 mAh / g, and the capacity retention rate after 500 cycles is ≥91%.

[0035] To help better understand the present invention, the following embodiments of this application disclose some specific implementation processes and comparative processes of the method for preparing battery anode materials based on waste SCR catalysts. The specific implementation processes and comparative processes include the exemplary embodiments 1 to 3 and Comparative Example 1.

[0036] Example 1 provides a method for preparing battery anode materials based on spent SCR catalysts, comprising the following steps: S1. Pretreatment of waste titanium-based SCR catalysts containing vanadium and tungsten components: Waste titanium-based SCR catalyst was mechanically ball-milled to obtain waste SCR micro powder with a particle size not exceeding 45 μm. The contents of tungsten trioxide (WO3) and vanadium pentoxide (V2O5) in the waste titanium-based SCR catalyst were 6.0% and 1.2%, respectively.

[0037] S2. The preparation of the precursor mixture slurry includes the following steps: Add 100g of the waste SCR micro powder prepared in step S1, 35g of glucose and 10g of sodium acetate to 400ml of distilled water, and then ultrasonically disperse at 450W ultrasonic power for 60min to obtain a precursor mixture slurry that is uniformly suspended and does not separate into layers. S3. The preparation of precursor microspheres includes the following steps: The precursor mixture slurry obtained in step S2 is fed into a spray dryer for drying. The inlet air temperature of the spray dryer is set to 200℃, the outlet air temperature is set to 100℃, and the atomizing disc speed is set to 20000rpm. After drying, the precursor microspheres are collected. S4. The preparation of the negative electrode material includes the following steps: The precursor microspheres collected in step S3 are placed in a tube furnace and protected by high-purity nitrogen gas. The atmosphere in the tube furnace is heated to 750°C at a heating rate of 5°C / min and pyrolyzed at a constant temperature for 6 hours. After natural cooling to room temperature, the negative electrode material is obtained. The negative electrode material includes vanadium and tungsten co-doped titanium dioxide grains, and the titanium dioxide grains are in situ wrapped by an amorphous carbon layer.

[0038] Example 2 differs from Example 1 only in that: in step S2, the mass ratio of waste SCR micro powder, glucose and sodium acetate is adjusted to 10:2:0.5, and the ultrasonic power is adjusted to 300W; in step S4, the atmosphere in the tube furnace is heated to 650°C at a heating rate of 5°C / min and pyrolyzed at a constant temperature for 8 hours. The remaining steps and parameters are the same as in Example 1.

[0039] Example 3 differs from Example 1 only in that: in step S2, the mass ratio of waste SCR micro powder, glucose and sodium acetate is adjusted to 10:5:1.5, and the ultrasonic power is adjusted to 600W; in step S4, the atmosphere in the tube furnace is heated to 800°C at a heating rate of 5°C / min and pyrolyzed at a constant temperature for 4 hours. The remaining steps and parameters are the same as in Example 1.

[0040] Comparative Example 1 differs from Example 1 only in that the waste titanium-based SCR catalyst containing vanadium and tungsten active components is replaced with commercially available pure chemical reagent grade titanium dioxide (without V and W elements). All other steps and parameters are the same as in Example 1.

[0041] Electrochemical performance tests and results analysis were conducted on sodium-ion batteries prepared using the negative electrode materials prepared in Examples 1 to 3 and Comparative Example 1. The test results are shown in the table below.

[0042] Table: Electrochemical performance test results of sodium-ion batteries prepared from the negative electrode materials prepared in Examples 1 to 3 and Comparative Example 1

[0043] As shown in the test results above, the sodium-ion battery prepared using the negative electrode material described in this invention exhibits superior electrochemical performance compared to the sodium-ion battery prepared using the same process with a negative electrode material made from pure titanium dioxide. Specifically, the three embodiments of this invention all show a first discharge specific capacity of no less than 262.0 mAh / g at a current density of 0.1 A / g, significantly higher than the 165.2 mAh / g of Comparative Example 1. The capacity retention rate after 500 cycles is all above 91.2%, significantly better than the 81.6% of Comparative Example 1. Furthermore, the rate performance is also superior, maintaining a capacity of over 162.4 mAh / g even at a high current density of 2 A / g, far exceeding the 78.1 mAh / g performance of Comparative Example 1.

[0044] From a cost and environmental perspective, the processing costs of Examples 1 to 3 are reduced by 70%, 75%, and 68% respectively compared to the baseline of Comparative Example 1. This invention uses spent SCR catalysts from industrial hazardous waste as raw materials, eliminating the need for complex acid-base leaching and component separation and purification steps required in traditional spent SCR catalyst recycling processes. Compared to traditional material preparation processes, the process is simpler. Simultaneously, the entire process generates no wastewater or harmful exhaust gases, effectively reducing processing costs. It solves the solid waste disposal problem of spent SCR catalysts and avoids the issue of consuming large amounts of virgin chemical raw materials during the preparation of virgin titanium-based anode materials. It truly achieves the full, zero-discharge, high-value utilization of industrial hazardous waste, possessing both outstanding environmental and economic benefits, and is suitable for large-scale industrial production applications.

[0045] In summary, the embodiments disclosed herein have at least the following technical effects: 1. Compared with the prior art, the present invention eliminates the need for complex acid and alkali leaching and heavy metal separation in the method and steps of recycling waste SCR catalysts, effectively shortening the process and generating no wastewater throughout the entire process, thus realizing the "full-volume zero-discharge high-value utilization" of industrial hazardous waste.

[0046] 2. The battery anode material prepared by the present invention exhibits excellent electronic / ionic dual conduction characteristics due to the high molecular-level dispersion of vanadium (V) and tungsten (W) elements in the original SCR catalyst. After in-situ pyrolysis, the vanadium (V) and tungsten (W) co-doped titanium dioxide anode formed exhibits excellent molecular / ionic dual conduction characteristics, overcoming the shortcomings of low capacity and poor conductivity of ordinary titanium-based anodes.

[0047] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing battery anode materials based on spent SCR catalysts, characterized in that, Includes the following steps: S1. Pre-treat the waste titanium-based SCR catalyst containing vanadium and tungsten components to obtain waste SCR micro powder; S2. A precursor mixture slurry is prepared by using the waste SCR micro powder, soluble carbon source and sodium source; S3. Spray dry the precursor mixture slurry to obtain precursor microspheres; S4. The precursor microspheres are placed in an inert atmosphere furnace and subjected to one-step high-temperature solid-phase pyrolysis to obtain the anode material.

2. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S1, the particle size of the waste SCR powder is ≤45μm.

3. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S2, the soluble carbon source is any one or more of glucose, sucrose, citric acid, or polyethylene glycol; the sodium source is any one of sodium carbonate, sodium acetate, or sodium hydroxide.

4. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S2, the mass ratio of the waste SCR micro powder, soluble carbon source and sodium source is 10:(2-5):(0.5-1.5).

5. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S2, the preparation method of the precursor mixture slurry includes the following steps: The waste SCR derivative, soluble carbon source, and sodium source are dissolved or dispersed together in deionized water, and the precursor mixture is obtained by ultrasonic dispersion.

6. The method for preparing battery anode materials based on spent SCR catalyst according to claim 5, characterized in that, The ultrasonic dispersion power is 300W to 600W, and the ultrasonic time is 40min to 80min; the solid content of the precursor mixture slurry is 13% to 25%.

7. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S3, the inlet air temperature of the spray dryer is 180℃~220℃, and the outlet air temperature is 90℃~110℃.

8. The method for preparing battery anode materials based on spent SCR catalyst according to claim 1, characterized in that, In step S4, the one-step high-temperature pyrolysis step includes: The inert atmosphere furnace is heated to 650℃~800℃ at a heating rate of 5℃ / min to pyrolyze the precursor microspheres, and then held at that temperature for 4h~8h.

9. A battery anode material prepared based on spent SCR catalyst, characterized in that, The titanium dioxide grains include vanadium and tungsten co-doped titanium dioxide grains, which are in situ encapsulated by an amorphous carbon layer.

10. The battery anode material prepared based on spent SCR catalyst according to claim 9, characterized in that, At a current density of 0.1 A / g, the initial discharge specific capacity of the negative electrode material is ≥260 mAh / g, and the capacity retention rate after 500 cycles is ≥91%.